Investigation of fluid flow in the space of a liquid-ring vehicle - Yu. M. Vertepov (Журнал інженерних наук)
The article is devoted to defining of hydrodynamic power losses of liquid in liquid-ring machine, in its free blade area. The losses may be compared with those in working wheel. The complexity of optimization energy characteristics of liquid-ring machine consists of thermodynamic losses of gas compression in working area and gasdynamic losses, connected with gas flow in machine windows, losses connected with gas movement across dead volume and inner clearances. All this losses must be accounted for optimal geometric sizes choice. This losses have different nature and depend on different geometric factors. This is the reason of low liquid-ring machines efficiency (about 35–40 %).